Pembuatan Aplikasi E-Learning Pada SMK Swasta Pariwisata Imelda - HENGKI TAMANDO SIHOTANG (Jurnal Mantik Penusa, 2017)
SMK Swasta Priwisata Imelda Medan is one of the private vocational schools in Medan. Learning system at SMK Swasta Priwisata Imelda Medan still use manual system which means the teaching and learning process is still bound by the time the subjects are available and must meet face-to-face with subject teachers. Subject material in the SMK Swasta Pariwisata Imelda Medan is quite difficult so that teachers and students need a long time in teaching and learning. to support an effective learning system at SMK Swasta Pariwisata Imelda Medan needs to be made an e-learning based learning system that is e-learning. the author uses the php language, mysql, dreamweaver and Xampp Control Panel Version 2.5.8, to provide solutions in the process of learning and teaching at SMK Swasta Pariwisata Imelda Medan in order to facilitate students and teachers in teaching and learning without the time limit provided by the school. Keywords: E-Learning, PHP, MySQL, Dreamweaver 8 and Xampp Control Pane Version 2.5.8.